Beyond curriculum knowledge: preparing Australian pre-service teachers' 'response-ability' to 21st century student diversity and working in partnership with families. Issue 2 (4th May 2022) - Woo, Eunice; Hadley, Fay; Fordham, Loraine
ABSTRACT: In Australia, pre-service teachers are those enrolled in an accredited teaching training course (four years undergraduate and two years postgraduate) to become a qualified teacher. The term 'classroom ready' is a common description when discussing pre-service teachers' capabilities upon completion of their course. In the Australian context, classroom ready means being equipped with curriculum content, pedagogical knowledge and skills, as well as catering for students with highly diverse needs and cultural backgrounds, and working in partnership with their families. This paper critiques recent policy developments, including the Australian Professional Standards for Teaching. These reforms will be outlined, together with key literature and current research on why developing family–school partnerships is a critical skill for pre-service teachers. We suggest that some of these reforms have led to the privileging of curriculum knowledge over the ability of pre-service teachers to work effectively with students and families in front-line contexts. Pre-service teachers need quality practical opportunities to exercise family–school partnership skills and become professionally competent to work with students and families from diverse backgrounds. With adequate attention to family–school partnerships in education policies and training courses, pre-service teachers can be better prepared to impact students' learning and contribute to quality teaching classrooms.